The Enforcement Strategy in The Sabah Maju Jaya (SMJ) Policy towards Achieving Sustainable Growth for Sabahans - Mohamad Ikhram Mohamad Ridzuan; Siti Nur Aafifah Hashim; Marja Azlima Omar (Human Resource Management Academic Research Society (HRMARS), 2023)
World economic growth, which is increasingly declining due to the impact of the COVID-19 controversy, has caused the Sabah State Government to launch the Sabah Maju Jaya (SMJ) Policy Development Plan on 29 March 2021 as one of the efforts to deal with this issue. Among the sectors given focus in the SMJ Plan are the development of human capital, economy and social well-being in Sabah. This is because, through the development of human capital, the economy and the sustainability of the people's well-being, it is believed to be able to produce people who are creative, critical and competitive for the needs of the present and the future immediately guaranteeing the sustainability of the country's economy. The qualitative research methods used in this study are a literature review and structured interviews. Among the informants are the Yang Berhormat Dato’ Ir. Shahelmy bin Yahya, who is Deputy Chief Minister III of Sabah. Professor Dr. Sity Daud is the Deputy Dean of Networking and Alumni at the National University of Malaysia and Professor Madya Datuk Ts. Dr. Ramzah Dambul is the Chief Executive Officer of the Sabah Development Research Institute (IDS), who is directly involved in contributing ideas, reviewing, proposing and analyzing policies and development frameworks in Malaysia and Sabah. Thus, this study was synthesized to identify the factors contributing to the well-being of the people in the state of Sabah to achieve the direction set in the SMJ Plan. The results of descriptive analysis and interviews with three informants found that there are three factors that affect the well-being of the people of Sabah, namely the issue of human capital, the income gap and the lack of facilities and infrastructure in the state. Therefore, to ensure that the SMJ Plan can achieve the direction set, this study suggests that the focus for development in the state of Sabah needs to be implemented holistically, including urban and rural areas.